IDEOLOGI DAN DOKTRIN MUHAMMADIYAH - Tu'aini, Tu’aini; Romelah, Romelah (​Institute for Researches and Community Services Universitas Muhammadiyah Palangkaraya, 2023)
Ideology is a set of systemic concepts from the way of thinking of a person or group of people as understanding, theories and ways to achieve goals. Muhammadiyah as a social organization also has an ideology as an organizational identity. The purpose of this article is to explain Muhammadiyah ideology and doctrine and found results namely: 1) Muqaddimah of the Articles of Association, namely the Muqaddimah Concept of the Articles of Association of Muhammadiyah (MADM) and the essence of MADM, the Muqaddimah of the articles of association of Muhammadiyah has 7 main ideas, the framework of the nature of the Muhammadiyah struggle and the definition of the muqaddimah of the ideology of Muhammadiyah. 2) Matan, Beliefs and Life Aspirations of Muhammadiyah, contains the concept and explanation of Matan, Beliefs and Life Aspirations of Muhammadiyah. 3) Muhammadiyah's personality contains 10 points.